The Accuracy and Acceptability of Students’ Post Editing of Idiomatic Expression Translation from English into Indonesia by Using U Dictionary - Cici Prima Yeswari; Havid Ardi (Universitas Negeri Padang, 2023)
This study aims to identify the accuracy and the acceptability of students’ post-editing of idiomatic expression translation from English into Indonesia by using U Dictionary. In this study, researchers used English students at Padang State University who had taken translation courses. Researchers use the translation test as a research instrument. This research method is descriptive qualitative. To analyze the data, the researcher identified the accuracy and acceptability of the students' post-editing results against the results of the U Dictionary. Then, the researcher calculates the average accuracy and acceptability. The researcher found that the level of accuracy and acceptability of post-editing for English students who have taken translation courses in translating idiomatic expressions is at the